Revisiting islamization of courses in economics with special emphasis on the operational aspect - Pramanik, Ataul Huq (Lifescience Global, 2016)
Knowledge immune from the moral and ethical principles based on a belief system as that of Islam has failed to address the hydra-leaded problems facing the world. Knowing about truth is possible not just by using acquired knowledge based on human reasoning or intellect. In other words, knowing is about 'becoming' or 'being'. The state of 'being' requires a continuous process of searching for the truth i.e. reality. However, given the diversity in human knowledge based simply on rationality and reasoning, it is a stupendous task to integrate the acquired knowledge of a discipline like that of economics with revealed knowledge i.e. on Islamic world view (IWV). This study attempts to identify the existing courses in Economics based on so-called conventional wisdom and suggest the process of integrating the knowledge of IWV usng the sources derived from the Quran, Sunnah, Qiyas and Ijtihad. As for the operationalization, this study involves different potential stake-holders such as, institutions, teachers, students, sharia scholars, parents, and lastly the markets as components of demand and supply side.